Proposta de reconfiguração estratégica de sistema financeiro no contexto de governança de tecnologia da informação (GTI): o caso de uma indústria do setor plástico - Santos, Simone Rodrigues dos (Universidade do Vale do Rio do Sinos, 2009)
This study developed a proposal for the strategic redesign of a finance system in the context of IT Governance supported by fuzzy logic algorithm. This study used a Design Research method in company of the plastic industrial sector. A new proposal was developed following these stages: 1 – Identification of current system; 2 – Identification of strategic variables; 3 – Quantification of strategic variables using matrixes; 4 – Calculation of the importance of strategic variables using a compensatory fuzzy logic algorithm. This stage created a ranking of importance or priorities. This ranking generated a redesigned system of Business Intelligence now used in the company. After the redesign in the IT context a necessity for financial disclosure was identified. XBRL language was used to do this and was validated by the company’s Controller as satisfactory. The following requisites were also identified: brand/image and costs optimization related to alignment of IT and strategy.
Keywords: governança de tecnologia da informação; sistema financeiro; algoritmo difuso; diffused algorithm; finance system; governance of information technology; business intelligence; Ciências Sociais Aplicadas